A Theoretical Account of the Coupling between Metal‐ and Ligand‐centred Spins. Issue 8 (23rd January 2023) - Roy, Sriparna; Paul, Satadal; Misra, Anirban
Abstract: This study addresses the magnetic interaction between paramagnetic metal ions and the radical ligands taking the [Cu II (hfac)2 (imVDZ)] and [M II (hfac)2 (pyDTDA)] (imVDZ=1, 5‐dimethyl‐3‐(1‐methyl‐2‐imidazolyl)‐6‐oxoverdazyl; hfac=(1, 1, 1, 5, 5, 5)hexafluroacetylacetonate; pyDTDA=4‐(2′‐pyridyl)‐1, 2, 3, 5‐dithiadiazolyl), (M=Cu, Ni, Co, Fe, Mn) compounds as reference systems. The coupling between the metal and ligand spins is quantified in terms of the exchange coupling constant ( J ) in the platform of density functional theory (DFT) and the wave function‐based complete active space self‐consistent field (CASSCF) method. Application of DFT and broken symmetry (BS) formalism results ferromagnetic coupling for all the transition metal complexes except the Mn(II) complex. This DFT‐BS prediction of magnetic nature matches with the experimental finding for all the complexes other than the Fe(II)‐pyDTDA complex, for which an antiferromagnetic coupling between high spin iron and the thiazyl ligand has been reported. However, evaluation of spin state energetics through the multiconfigurational wave function‐based method produces the S=3/2 ground spin state for the iron‐thiazyl in parity with experiment. Electronic structure analyses find the overlap between the metal‐ and ligand‐based singly occupied molecular orbitals (SOMOs) to be one of the major reasons attributing to different extent of exchange coupling in the systems under investigation. Abstract : In some cases, the metal‐based singly occupied molecular orbitals (SOMOs) belonging to the e g e_g level are less favourable than those in the t 2 g t_2g level for overlap ( Sab ) with the ligand‐based SOMOs, leading to a variation in the extent of the exchange coupling constant ( J ) and a subsequent ferro‐/antiferromagnetic nature of the octahedral metal‐radical compounds.